2020
DOI: 10.1038/s42003-020-1101-3
|View full text |Cite
|
Sign up to set email alerts
|

The cardiolipin-binding peptide elamipretide mitigates fragmentation of cristae networks following cardiac ischemia reperfusion in rats

Abstract: Mitochondrial dysfunction contributes to cardiac pathologies. Barriers to new therapies include an incomplete understanding of underlying molecular culprits and a lack of effective mitochondria-targeted medicines. Here, we test the hypothesis that the cardiolipin-binding peptide elamipretide, a clinical-stage compound under investigation for diseases of mitochondrial dysfunction, mitigates impairments in mitochondrial structure-function observed after rat cardiac ischemia-reperfusion. Respirometry with permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 108 publications
(155 reference statements)
1
58
0
Order By: Relevance
“…Additionally, improved bioenergetic efficiency would reduce the overall need for carbon substrates to support metabolism, which may also contribute to the reductions in various metabolite concentrations observed. These suppositions are in agreement with prior pre-clinical [11,13,49,50] and clinical [51,52] data in settings other than Barth syndrome, indicating that elamipretide treatment can bring about a more efficient bioenergetic state.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, improved bioenergetic efficiency would reduce the overall need for carbon substrates to support metabolism, which may also contribute to the reductions in various metabolite concentrations observed. These suppositions are in agreement with prior pre-clinical [11,13,49,50] and clinical [51,52] data in settings other than Barth syndrome, indicating that elamipretide treatment can bring about a more efficient bioenergetic state.…”
Section: Discussionsupporting
confidence: 89%
“…The loss of mature cardiolipin in Barth syndrome results in cascades of cellular dysfunction, including loss of energy and redox homeostasis, calcium overload, and cell death (for review see Sabbah [3]). Improved mitochondrial structure [13] and ETC/supercomplex function [33] with elamipretide are also expected to improve the local availability of oxidized FAD and NAD + cofactors essential for complete β-oxidation of fats [47,48]. All of these factors may contribute to the decreases in plasma and urine acylcarnitines, as well as the trends for lower acetylcarnitine, 3-methylglutaconate, and 3-hydroxybutyrate observed in this study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…There, it binds to cardiolipin via electrostatic and hydrophobic interactions, 15 and is hypothesized to sustain the cristae network and remediate bioenergetic dysfunction. 16 SS-31 has shown benefit in preclinical mitochondrial disorders and heart failure. 15,[17][18][19][20] We performed a randomized, double-blind, placebocontrolled crossover trial with an open-label extension to test the clinical efficacy and safety of daily administration of elamipretide in individuals with genetically confirmed Barth syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies inaccurately described ELAM as having antioxidant properties, [19][20][21] although more recent work has demonstrated that ELAM actually reduces production of superoxide and H2O2 particularly where overproduction resulted from dysfunctional mitochondria [22,23]. Studies in isolated mitochondria, cells and intact organs reveal improved ETC flux, reduced mitochondrial generation of reactive oxygen species (ROS; H2O2), and elevated ATP generation with ELAM treatment after ischemic insult and heart failure [16,24,25]. In skeletal muscle, treatment with ELAM prevented the increase in mitochondrial oxidative stress and muscle wasting associated with disuse atrophy in mouse hindlimb and diaphragm.…”
mentioning
confidence: 99%